2022
DOI: 10.1109/tfuzz.2020.3046335
|View full text |Cite
|
Sign up to set email alerts
|

Event-Based Dissipative Control of Interval Type-2 Fuzzy Markov Jump Systems Under Sensor Saturation and Actuator Nonlinearity

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…A simulation study showed that the combined JITL-PCA models outperformed PCA in the analyzing of nonlinear signals [26]. In addition, neural network methods and the stochastic hidden Markov model (HMM) were studied to improve FD performance of dynamic systems [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…A simulation study showed that the combined JITL-PCA models outperformed PCA in the analyzing of nonlinear signals [26]. In addition, neural network methods and the stochastic hidden Markov model (HMM) were studied to improve FD performance of dynamic systems [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…When this issue is considered, the general T-S fuzzy modeling scheme cannot achieve the desired results [15]. The IT2 fuzzy model was developed because of its good proxy for nonlinear systems with parameter uncertainty [29][30][31][32][33][34][35][36][37]. The problem of the FD filtering method is proposed with event-based, which is the application in IT2 fuzzy theory under the framework of networked timedelay control systems [29].…”
Section: Introductionmentioning
confidence: 99%
“…Combining a set of IF-THEN rules with some fuzzy sets, makes it possible to approximate nonlinear systems with high precision using a series of linear subsystems. As a result, recent years have seen an increase in research interest in the control issues associated with T-S fuzzy systems [2]- [6]. The authors in [5] have discussed the stability of a T-S fuzzy system with state quantization under exponential dissipation using a non-fragile sampled-data control.…”
Section: Introductionmentioning
confidence: 99%